The effect of increased maximal upper body strength on sprint kayak ergometer performance - Klitgaard, K.; Kristiansen, M.; de Zee, M.; Jakobsen, J. V. (VIII Congreso Internacional De Entrenadores De Piragüismo en Aguas Tranquilas, 2022)
BACKGROUND AND AIM: Optimal performance in the 200m flatwater sprint kayak discipline is heavily dependent on the ability to generate anaerobic power. As anaerobic power in kayaking can be expressed as maximal power output per stroke, it is inherently limited by muscle strength, more specifically upper body strength. Therefore, the aim of the present study was to investigate whether an increase in maximal upper body strength would elicit a concomitant change in 200m kayak sprinting performance.